Baptista chaotic cryptosystem based on alternate superior dynamic lookup table. (17th November 2019) - Verma, Deepak Kumar; Rani, Mamta; Tyagi, Rajesh Kumar; Sagar, Bharat Bhushan
Abstract: Chaotic cryptosystems are using for securing text data and images over the network. In 1998, M S Baptista suggested a chaotic cryptosystem based on partitioning the visiting interval of chaotic orbits of the logistic map, which attracted much attention. In 2002, K W Wong presented a prompt chaotic cryptosystem based onthe dynamic lookup table using a logistic maptoimprove the security in Baptista type cryptosystem. In 2004, Alvarezet al. [1] found that Wong's cryptosystem [15] is not resistant tochosen-plaintext and known-plaintext attacks. To improve the security of the dynamic lookup table, weintroduce an alternate dynamic lookup table that will be more secure in context to the existing system.